Mental motivation and its relationship to the performance of the skill of receiving the transmitter in volleyball - ساية سامي أ.د. لمى سمير (الرياضة المعاصرة)
From here emerged the importance of research in conducting a study that lies in the role (mental motivation) in the educational process, especially in the performance of the skill of receiving transmitter in volleyball. Through the experience of the two researchers in volleyball, it was noted that there is a weakness in the level of students for the skillful performance of volleyball, especially in the skill of receiving the transmitter, which calls for the necessity of caring for the mental motivation in order to serve the educational process, especially the skill of receiving the transmitter , Therefore, the two researchers decided to experiment with the mental motivation of the learners, which increases the enthusiasm of the learner through the use of their mental processes to receive and understand information, and thus this may affect their learning of skills, especially the skill of receiving the transmitter. The study aimed to identify the values ​​of mental motivation and the skill of receiving transmissions in volleyball to the research sample and to find the relationship between them. The researchers assumed that there was no statistically significant relationship between mental motivation and the performance of the skill of receiving volleyball. The two researchers used the descriptive approach to its suitability for the research problem. As for the research sample, it was determined in selecting (33) students out of (103) students. The research sample was chosen in a random, unorganized way (the lottery method). The researchers concluded that there is a strong correlation between mental motivation and the skill of receiving transmitter in volleyball, and the two researchers recommend relying on mental motivation when teaching learners the skills of volleyball, especially the skill of receiving transmitter.